ARIH1 signaling promotes anti-tumor immunity by targeting PD-L1 for proteasomal degradation - Wu, Youqian; Zhang, Chao; Liu, Xiaolan; He, Zhengfu; Shan, Bing; Zeng, Qingxin; Zhao, Qingwei; Zhu, Huaying; Liao, Hongwei; Cen, Xufeng; Xu, Xiaoyan; Zhang, Mengmeng; et al. (Nature communications, 2021)
Cancer expression of PD-L1 suppresses anti-tumor immunity. PD-L1 has emerged as a remarkable therapeutic target. However, the regulation of PD-L1 degradation is not understood. Here, we identify several compounds as inducers of PD-L1 degradation using a high-throughput drug screen. We find EGFR inhibitors promote PD-L1 ubiquitination and proteasomal degradation following GSK3α-mediated phosphorylation of Ser279/Ser283. We identify ARIH1 as the E3 ubiquitin ligase responsible for targeting PD-L1 to degradation. Overexpression of ARIH1 suppresses tumor growth and promotes cytotoxic T cell activation in wild-type, but not in immunocompromised mice, highlighting the role of ARIH1 in anti-tumor immunity. Moreover, combining EGFR inhibitor ES-072 with anti-CTLA4 immunotherapy results in an additive effect on both tumor growth and cytotoxic T cell activation. Our results delineate a mechanism of PD-L1 degradation and cancer escape from immunity via EGFR-GSK3α-ARIH1 signaling and suggest GSK3α and ARIH1 might be potential drug targets to boost anti-tumor immunity and enhance immunotherapies. The regulation of PD-L1 via proteasomal degradation is unclear. Here, the authors show that EGFR inhibition activates GSK3 α to promote PD-L1 phosphorylation, which leads to PD-L1 ubiquitination and proteasome mediated degradation by ARIH1 E3 ligase.